Pengaruh Pelatihan Kerja Dan Literasi Digital Terhadap Kinerja Pegawai Badan Pusat Statistik Kota Tasikmalaya - Iyas Muhadib; Arga Sutrisna; Kusuma Agdhi Rahwana (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the effect of job training and digital literacy on employee performance at the Central Bureau of Statistics for the City of Tasikmalaya. This research uses quantitative methods. The type of data used is primary data and secondary data, with a sample of 41 respondents from the employees of the Central Bureau of Statistics for the City of Tasikmalaya, and using the saturated sample method. The data analysis tool used in this study was SPSS Version 25. Data collection techniques used literature studies, field studies: interviews, questionnaires. The results of the study show that Job Training and Digital Literacy simultaneously have a significant effect on Employee Performance. Job Training partially has a significant effect on Employee Performance. Digital Literacy partially has no significant effect on Employee Performance.